PENGARUH UKURAN BIBIT DAN JENIS PUPUK ORGANIK TERHADAP HASIL UMBI TANAMAN TALAS BENENG (Xanthosoma undipes K.Koch) - Kartina AM; Nuniek Hermita; Ellena Claudia Agustin (Jurnal Agroekoteknologi, 2017)
The research was aimed to know the effects of seedling size and kind of organic fertilizer to the plant tuber yield of talas beneng (Xanthosoma undipes K. Koch). Research was conducted from August 2016 until January 2017 in KampungJuhut, KarangTanjung Sub-district, Pandeglang Regency, Banten Province. This research used Randomized Completely Block Design (RCBD) with two factors and three replications. The first factor was seedling size (D) wich consisted three levels namely D1 : 1 cm – 3.5 cm, D2 : 4 cm – 6.5 cm, and D3 : 7 – 9.5 cm. The second factor was kind of organic fertilizer (P) wich consisted three levels namely P1 : chicken manure fertilizer, P2 : goat manure fertilizer and P3 : organic fertilizer (pertoganik). The parameters observed were tuber weight, tuber diameter, tuber length, number of tuber secondary, oxalate content . The resultsshowed that the size of the seedling diameter giving the best influence on the long tuber length of the taro tuber (Xanthosomaundipes K. Koch) was on the D3 treatment (7 – 9.5 cm). The treatment of organic fertilizer type of chicken manure (P1) gave the best influence to the parameters of the number of secondary tubers. There was no interaction between seed size and type of organic fertilizer on all parameters observed.Keyword: Talasbeneng (Xanthosoma undipesK. Koch), Seedling size, Organicfertilizer